Solitary extradigital glomangioma with thrombus presenting as a painful nodule - Indu Kumari; Swosti Mohanty; Uday S Khopkar; Priya Charak (Wolters Kluwer Medknow Publications, 2019)
Glomangioma, currently termed as glomuvenous malformation, is a rare type of venous malformation (VM) with a rim of glomus cells around the dilated vessels. This glomus cell lesion is not usually as painful as solid glomus tumor. Rarely, thrombus may be seen in the vessels like other VMs. A male with adult-onset extradigital glomangioma presented with a painful nodule with thrombus seen on histopathology. The thrombus was responsible for the tenderness of the lesion, and its presence confirms it to be a malformation than a tumor.